The Influence of DER, ROA, EPS, and NPM on Stock Prices in IDX ENERGY Sector Companies in 2017–2022 - Yosep Yudianto; Sony Kuswandi; Haris Sandi Yudha (Lafadz Jaya Publisher, 2025)
This study aims to analyze the influence of Debt-to-Equity Ratio (DER), Return on Assets (ROA), Earnings per Share (EPS), and Net Profit Margin (NPM) on stock prices of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2017–2022. A quantitative approach with an explanatory method was employed in this study. The research sample consisted of 26 companies selected through purposive sampling, resulting in a total of 156 annual observations. Secondary data were obtained from annual financial reports published on the official websites of IDX. Data analysis was conducted using multiple linear regression with the help of SPSS, along with classical assumption testing to ensure model validity. The results indicate that simultaneously, the four independent variables have a significant effect on stock prices. Partially, DER has a negative and significant effect, ROA and EPS have positive and significant effects, while NPM does not significantly influence stock prices. The adjusted R² value of 0.392 implies that 39.2% of the variation in stock prices can be explained by this model. These findings reinforce the relevance of financial ratios as tools for fundamental stock analysis. The practical implication of this study encourages corporate management to enhance asset efficiency and earnings per share performance to attract investors. The study also contributes theoretically to the development of stock valuation models based on financial ratios in the energy sector.